Plummer-Vinson syndrome presenting as squamous cell carcinoma of esophagus - Lanke, Gandhi; Koduru, Pramoda; Bhutani, Manoop S. (Journal of Digestive Endoscopy, 2016)
Plummer-Vinson syndrome (PVS) also known as Paterson-Brown-Kelly syndrome is a rare syndrome which comprises iron deficiency anemia, dysphagia, and esophageal webs. The pathogenesis of PVS is not clear. Iron deficiency anemia is essential for diagnosis of PVS. If left untreated, there is an increased risk of developing pharyngeal or esophageal cancer in about 10% of patients. There are no strict guidelines for endoscopic surveillance in patients with PVS. Iron replacement can improve dysphagia and potentially lead to regression of esophageal webs. In this case report, we present a patient who had long-standing dysphagia for years which progressed to squamous cell cancer of esophagus by the time she sought medical treatment.
Keywords: Dysphagia; esophageal cancer; iron deficiency anemia; Paterson-Brown-Kelly syndrome